(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
The Chinese legislator has designed a complex regulatory framework to regulate the use of artificial intelligence and build a new model of national governance capable of integrating the political, legal, industrial, commercial, financial, environmental, and social credit sectors. Efforts are aimed at developing an increasingly trustworthy and secure AI, the foundation of an intelligent rule of law. The intelligentization of justice operates on the construction of databases, the regulation of the telematic process, the creation of Mobile Micro Courts and internet courts, and goes as far as the development of an AI-assisted case management system. This process of intelligentization is not only a technical tool to make conflict management more efficient but also a response to the needs of the judicial responsibility system. We are moving towards a new paradigm of digital justice, which is declined according to the features of Chinese legal culture.